DESIGN AND EVALUATION OF GUARGUM - BASED TIMOLOL MALEATE OCULAR INSERT - Kumar, Sunil; Issarani, Roshan; Nagori, B P (INDONESIAN JOURNAL OF PHARMACY, 2015)
The objective of this study was to prepare ocular inserts of timolol maleate using guar gum as a polymer. Timolol maleate ocular inserts were prepared by solvent casting method using guar gum in different proportions (0.25% w/v, 0.50% w/v , 75 % w/v and 1.0% w/v). The prepared formulations were evaluated for thickness, weight variation, percentage drug content, surface pH, folding endurance, percentage moisture absorption and loss, percentage swelling, mechanical strength and in vitro transcorneal permeation. In-vitro transcorneal permeation study was performed on goat cornea using modified Franz diffusion cell. The inserts were found to be of uniform thickness (ranging from 41.12±0.04µm to 79.90±0.03µm) and weight (0.84±0.07 mg to 2.11±0.09 mg). The % drug content in the inserts was found to be varied between 98.69±0.58to 96.37±0.58. The cumulative % drug releases from the formulation ranged from 50.22±1.41 to 97.72±0.67over a period of 24 h. In-vitro transcorneal study revealed that an increase in concentration of polymer slows down the release of timolol maleate from the formulation. Ocular inserts using guar gum as a polymer were successfully prepared and can be effectively used for sustain ocular delivery over a period of 24 h.Key words: Guar gum, in vitro transcorneal permeation study, ocular insert, timolol maleate, sustained release